2016
DOI: 10.1128/aac.01414-15
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Colistin Dose on Global Cure in Patients with Bacteremia Due to Carbapenem-Resistant Gram-Negative Bacilli

Abstract: The increasing prevalence of multidrug-resistant (MDR) nosocomial infections accounts for increased morbidity and mortality of such infections. Infections with MDR Gram-negative isolates are frequently treated with colistin. Based on recent pharmacokinetic studies, current colistin dosing regimens may result in a prolonged time to therapeutic concentrations, leading to suboptimal and delayed effective treatment. In addition, studies have demonstrated an association between an increased colistin dose and improv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
25
1
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 21 publications
3
25
1
2
Order By: Relevance
“…Whether use of a loading dose and higher daily doses is associated with improved efficacy is again controversial. No comparative randomized trials have been found, although several observational or quasi-experimental studies with discrepant results have been published (269)(270)(271)(272)(273)(274)(275)(276). In most studies, renal toxicity was more frequent with higher doses.…”
Section: Polymyxinsmentioning
confidence: 99%
“…Whether use of a loading dose and higher daily doses is associated with improved efficacy is again controversial. No comparative randomized trials have been found, although several observational or quasi-experimental studies with discrepant results have been published (269)(270)(271)(272)(273)(274)(275)(276). In most studies, renal toxicity was more frequent with higher doses.…”
Section: Polymyxinsmentioning
confidence: 99%
“…In a retrospective, single-center cohort study by Falagas and colleagues, it was concluded that mortality among patients who received an average daily colistin dose of 100 mg CBA (38.6%) was higher than the mortality among patients who received 200 mg CBA (27.8%) and 300 mg CBA (21.7%) (15). Furthermore, Gibson and colleagues, using a classification and regression tree analysis-derived cutoff, determined that patients who received Ͼ4.4 mg CBA/kg/day based on IBW were more likely to achieve global cure, microbiological clearance, and day 7 survival (16). As such, the findings of the present study appear to be contrary to those of previous studies, since obese patients were being dosed more aggressively but had similar or worse outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Assuming a global cure rate of 50% in the nonobese group (16,28), 166 patients would be needed to achieve an 80% power with an alpha of 0.05 in a one-tail test to detect a 20% absolute difference between groups. Categorical data were analyzed using either the 2 test or Fisher's exact test, as appropriate.…”
Section: Methodsmentioning
confidence: 99%
“…y Acinetobacter baumannii complex y como resistente con una CIM > 2 mg/l (17,18) . Es importante destacar que el uso de colistina debería reservarse para el tratamiento específico de infecciones producidas por microorganismos resistentes a los betalactámicos, en particular los carbapenemes, o como parte del tratamiento empírico de pacientes con infecciones graves (siempre asociada a otros antimicrobianos) si se sospecha la participación de un microorganismo con ese perfil de resistencia (4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19) .…”
Section: Espectro Antibacterianounclassified
“…La resistencia a colistina se explica por mutaciones en los genes que conducen a modificaciones en la capa de LPS, sitio de acción de esta molécula (13,20) . Adicionalmente a esta modalidad, en noviembre de 2015 se informó sobre la aparición de un nuevo mecanismo de resistencia a colistina a través de plásmidos, relacionado al gen mcr-1 (Mobile Colistin Resistance), productor de una enzima responsable de la resistencia, por lo que se puede diseminar fácilmente la misma a otras bacterias (9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22) . Desde abril de 2016 en nuestro continente se ha identificado este mecanismo de resistencia en E. coli y otras enterobacterias, aisladas a partir de muestras de alimentos y animales, pero también de muestras clínicas de pacientes.…”
Section: Mecanismos De Resistenciaunclassified